2005
DOI: 10.1177/0891243204272153
|View full text |Cite
|
Sign up to set email alerts
|

Beards, Breasts, and Bodies

Abstract: Gender is commonly thought of as dependent on sex even though there are occasional aberrations. Interviews with female-to-male trans people, however, suggest that sex and sex characteristics can be understood as expressions of gender. The expression of gender relies on both behavior and the appearance of the performer as male or female. When sex characteristics do not align with gender, behavior becomes more important to gender expression and interpretation. When sex characteristics become more congruent with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 172 publications
(31 citation statements)
references
References 15 publications
1
30
0
Order By: Relevance
“…The masculinities that women do not have such as aggressiveness and forcefulness, deny them the opportunity to be taken seriously. Thatho's gains in terms of male privilege supports recent academic work that show how trans men benefit at work to the detriment of women workers (Dozier 2005;Schilt 2006). Schilt (2006) argues that many of the trans men respondents in her study found themselves receiving more authority, respect and reward when they gain social identities as men.…”
Section: Francissupporting
confidence: 75%
“…The masculinities that women do not have such as aggressiveness and forcefulness, deny them the opportunity to be taken seriously. Thatho's gains in terms of male privilege supports recent academic work that show how trans men benefit at work to the detriment of women workers (Dozier 2005;Schilt 2006). Schilt (2006) argues that many of the trans men respondents in her study found themselves receiving more authority, respect and reward when they gain social identities as men.…”
Section: Francissupporting
confidence: 75%
“…More recently, researchers have investigated the intersection between gender identity and other single social identities such as sexual identity (e.g., Bockting, Benner, & Coleman, 2009;Chivers & Bailey, 2000;Hill, 2007), racial/ethnic identities (e.g., Dozier, 2005;Erich, Tittsworth, Colton-Meier, & Lerman, 2010;Roen, 2001;Rosario, 2004;Schilt, 2006;Singh, 2013), or SES (e.g., Gehi & Arkles, 2007), individually. Conversely, literature similar to that of Dozier (2005) and Schilt (2006) examined more than one social identity of trans individuals (e.g., race/ethnicity, height, sexuality) but only focused on trans men. There is a lack of comprehensive research on the simultaneous influences and interrelatedness of different identities and mental health outcomes within the trans population.…”
Section: Multiple Identities and Mental Healthmentioning
confidence: 99%
“…transgender issues and lives. Since this time, published scholarship on transgender and transsexual individuals has slowly become more common (e.g., Dozier, 2005;Girschick, 2008;Hines, 2006;Rubin, 2004;Schilt, 2006;Shapiro, 2004). As focus on transgender and transsexual individuals emerges in sociology, partners of transgender and transsexual individuals have not yet appeared as intelligible subjects within published sociological research.…”
mentioning
confidence: 99%